Future of work and education in 21st century. Coworking as learning space - Glenda Galeotti (Firenze University Press, 2019)
The transformation of the labour market has caused rapid unavoidable effects on educational and training needs. As a part of the debate on the future of work, learning and skills in the 21st century, this contribution focuses on learning processes in coworking as shared workplaces where it is possible to combine different professional skills in a productive, social and learning environment. In fact, coworking spaces can interpret the changes in our society, offering an alternative perspective on labour based on collaboration and meaningful connections between people, as well as self-directed, self-regulated, and socially integrated educational pathways.   Futuro del lavoro ed educazione del XXI secolo. Il coworking come spazio di apprendimento Le trasformazioni in atto nel mondo del lavoro producono effetti rapidi ed ineludibili sulle istanze educative e formative. Attraversando il dibattito sul futuro del lavoro, l'apprendimento e le competenze del XXI secolo, l'articolo si sofferma sui processi formativi che si sviluppano nei coworking, luoghi di lavoro condivisi capaci di coniugare professionalità differenti in un ambiente sociale, produttivo e di apprendimento. Questi sembrando in grado di interpretare i mutamenti in atto nella nostra società, proponendo una visione alternativa di lavoro basata sulla collaborazione e sulle connessioni significative fra le persone, nonché percorsi educativi autodiretti, autoregolati e socialmente integrati.